Parametric Study of Silicon Based Optical Leaky-Wave Antenna - Hummadi, Ali A.; Fyath, R. S. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Parametric study is presented for 1550 nm CMOS compatible optical leaky wave antenna. The antenna is designed with Si3N4 waveguide perturbed periodically with silicon. The silicon perturbations are used to transform the guided mode into a leaky mode radiated to the surrounding space. Simulation results are obtained using the commercial software package CST STUDIO SUITE 2012 and indicate clearly the strong dependence of radiation parameters on the number and dimensions of the silicon perturbations.